Achieving sustainable energy solution for mosques in Perak through micro-scale solar technologies: A Community-Based Approach (CBA - Ahmad, Nur Azfahani; Khalid, Mohd Khazli Aswad; Wan Hamdan, Wan Samsul Zamani; Mohd Yaacob, Hamdi Rahman; Ismail, Nur Sufiyah (Journal of Islamic, Social, Economics and Development, 2024)
This research presents a community development project that utilize a community-based approach (CBA) to emphasize energy-saving initiatives with the aid of micro-scale solar technology systems at two mosques in Perak. The primary goal of these projects is to increase community development among local residents while promoting green energy practices, fostering a sense of commitment toward energy sustainability. The study focuses on two mosque communities in Perak, employing a mixed-method approach that actively involves local participants throughout the project. This initiative aligns with Sustainable Development Goal (SDG) No. 7, which emphasizes in providing affordable and sustainable energy to communities. The project incorporated action-based research on-site, with volunteers and stakeholders—including mosque management, UiTM Perak branch, and local residents—collaborating under a university-social responsibility (USR) program. The positive outcomes of this project include mosque’ community empowerment, demonstrated through tangible benefits such as enhanced community development, improved lighting conditions, and reduced electricity bills during nighttime. These benefits stem from the self-sufficient electricity generated by the small-scale solar solutions installed at the mosques. By utilizing solar technology systems ranging from 10 to 300 watts, the mosques have decreased their reliance on traditional energy sources, contributing to energy security and achieving a 5% to 9% reduction in monthly electricity bills. This project has not only showcased the advantages of solar energy but has also raised broader energy awareness within the mosque communities in Perak. In the near future, the widespread adoption of solar energy technologies is expected to contribute to more sustainable mosques in Malaysia and further enhance community development through sustainable practices.